Convergent and Discriminant Validities of SCBE-30 Questionnaire Using Correlated Trait–Correlated Method Minus One - Fernandes, Marília; Santos, António J.; Antunes, Marta; Fernandes, Carla; Monteiro, Lígia; Vaughn, Brian E.; Veríssimo, Manuela (Frontiers in Psychology, 2020)
Correlated Trait-Correlated Method Minus One was used to evaluate convergent and discriminant validity of Social Competence Behavior Evaluation questionnaire (Social Competence, Anger-Aggression, Anxiety-Withdrawal) between multiple raters. A total of 369 children (173 boys and 196 girls; Mage = 55.85, SDage = 11.54) were rated by their mothers, fathers and teachers. Results showed more convergence between parents than parent-teacher ratings. Mother-teacher share a common view of child behavior that is not shared with father. Parents had more difficulty distinguishing internalizing and externalizing behaviors (especially fathers). Measurement invariance across child sex was explored, results imply that differences between boys and girls were not due to measure. Girls (compare to boys) were described as more social competent by their fathers and teachers, while boys as more aggressive by mothers and teachers.